BLENDED LEARNING/ FLIPPED CLASSROOM USING TAKLIM AL LATHIF LEARNING MANAGEMENT SYSTEM DURING THE NEW NORMAL PERIOD - Sri Tubilah Noor (Green Publisher, 2022)
The writing discusses how the management model of the blended learning/flipped classroom learning system using the Learning Management System in the New Normal period at the Al lathif Islamic International School. This research implements the blended learning method practically and efficiently by using a learning management system. The objectives to be achieved in this study are to obtain an overview and analyze the implementation of the Blended Learning/Flipped Classroom system management model. The learning process is carried out through a learning management system, both synchronous and asynchronous., using a variant of Learning methods such as: Live Synchronous Learning (LSL), Virtual Synchronous Learning (VSL), Collaborative Asynchronous Learning (CAL), Self-directed Asynchronous Learning (SAL). The research method used is the descriptive qualitative method by conducting interviews with teachers, students, administrators & principals. The learning process is carried out by combining face-to-face and online learning. Data collection techniques in interviews, documentation, and literature studies show that learning using the blended learning method through LMS has several advantages and obstacles. Test the validity of the data is done by triangulation. Techniques of data processing carried out with the stages of data reduction, data presentation, verification, and conclusion. The main reason of using this is unique management model system is to simplify the learning plan into three aspects, learning objectives, learning activities and evaluation.